Pengaruh Kualitas Layanan Terhadap Kepuasan Nasabah Pada Bank Syariah Indonesia (BSI) Kantor Cabang Sorong - Muh Noval Justika; Rokhimah (Prodi Ekonomi Syariah IAIN Sorong, 2025)
This study aims to determine the effect of service quality on customer satisfaction at Bank Syariah Indonesia (BSI) Sorong Branch Office. The method used was quantitative, involving 100 respondents determined using the Lemeshow formula. Data were collected through questionnaires and analyzed using simple linear regression to test the proposed hypotheses, using SPSS version 25. The results showed a significant effect between service quality and customer satisfaction, with a calculated t-value of 11.287 > t-table 1.984, and a significant value of 0.000 < 0.05. This indicates that the better the service quality provided, the higher the level of customer satisfaction. The conclusion of this study is that service quality has a positive impact on customer satisfaction. Therefore, it is recommended that Bank Syariah Indonesia Sorong Branch Office continue to improve and maintain its service quality to create customer satisfaction. This research is expected to serve as a reference for the company in maintaining and improving the quality of its services to attract new customers and retain existing ones.